Estimation of Cytotoxicity and Genotoxicity of long acting Bronchodilator: Salmeterol Xinafoate Nanoparticles (Nanotoxicity Study) - RAGIA M. HEGAZY; EMAN M.FARUK; AMINA A. FARAG; LAMIAA M.SHAWKY (International Journal of Pharma and Bio Sciences, 2018)
Nanoparticles (NPs) are now extensively used in different fields with inadequate knowledge on their toxicity. Salmeterol is a potent long acting-β agonist (LABA) used for the management of pulmonary disorders. Sothe present study was aimed to evaluating in vitro cytotoxicity and genotoxicity of nano salmeterol xinafoate nebulization. Blood samples from ten healthy volunteers were cultured and divided into two equal groups: control untreated group and other treated with a dose of nano salmeterol (50µg/ml) and incubated at 37°C for 24 hour then evaluated for local and systemic toxicity. Genotoxic study by using Comet assay and chromosomal karyotype was done. Morphological analysis of nano-sized salmeterol xinafoate particles was performed by Transmission Electron Microscopy (TEM) and Anderson Cascade Impactor (ACI) in which the average particle size was in the range of 300–500 nm. Our results showed that there was a- non significant decrease (p>0.0.05) in the level of antioxidant enzymes: ROS, GSH, SOD, and Catalase; while, there was significant increase (p<0.0.05) in the level of Lipid Peroxidation (LPO). The Comet assay indicated that cells treated with Salmeterol xinafoate NP induced non-significant increase in percentage tail DNA damage compared to control (p>0.0.05), Also, the chromosomal aberration was non-significant increase (p>0.0.05). So our study concluded that this dose of nano-salmeterol xinafoate NP nebulizer may be tolerated by asthmatic patients and further studies need in diseased patients and with different organs.